Transcriptome analysis of seed development in apomictic Paspalum notatum - Felitti, Silvina Andrea (2015)
Fil: Felitti, Silvina Andrea. Universidad Nacional de Rosario. Facultad de Ciencias Agrarias. Laboratorio de Biología Molecular; Argentina.